Association between pregravid liver enzyme levels and gestational diabetes in twin pregnancies: a secondary analysis of national cohort study - Jae-Young Park (Nature Portfolio, 2021)
Abstract Multiple pregnancies are prone to gestational diabetes mellitus (GDM). This study investigated the association between pregravid liver enzyme levels and the development of GDM in a twin pregnancy. Women who had the National Health Screening Examination and delivered their twin babies within one year were enrolled. Pregravid liver enzyme levels were divided into high and low level. Risks for developing GDM by high levels of liver enzymes were analyzed, in subgroups by pregravid obesity or metabolic syndrome. Among the 4348 twin pregnancies, 369 women (8.5%) developed GDM not requiring insulin treatment (GDM − IT), and 119 women (2.7%) developed GDM requiring insulin treatment(GDM + IT). High levels of pregravid GGT and ALT were related to risks of GDM + IT not only in women with obesity or metabolic syndrome (odds ratio[OR] 6.348, 95% confidence interval [CI] 2.579–15.624 and OR 6.879, 95% CI 2.232–21.204, respectively), but also in women without obesity (OR 3.05, 95% CI 1.565–5.946) or without metabolic syndrome (OR 3.338, 95% CI 1.86–5.992), compared to in women with low levels of those. However, there were no significant associations in the pregravid ALT and GGT levels and risks for development of GDM − IT, unrelated to pregravid obesity or metabolic syndrome. Therefore, this study suggests that women with high levels of pregravid GGT and ALT need to recognize their increased risk of GDM + IT, regardless of pregravid obesity or MetS, when they get pregnant twin.